EFEKTIVITAS PENGGUNAAN KAHOOT! DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS V SDN NYORMANIS 2 - Fani Nur Anggita; Adhiba Anis Safitri; Fariza Putri Nabila; Amelia Khoiruna; Aisyiyah Siti Rodiyah; Nurhandayany; Ika Dian Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research investigates the effectiveness of Kahoot! in fostering fifth-grade students' learning interest at SDN Nyormanis 2. The study addresses the problem of low student interest, a crucial internal factor influencing academic success. Employing a quantitative approach with an experimental design, data was collected using a closed questionnaire. This instrument, based on a Likert scale (strongly agree (4), agree (3), disagree (2), strongly disagree (1)), measured student responses before and after Kahoot! implementation across indicators such as enjoyment, involvement, attraction, and attention. The findings indicate a significant increase in student learning interest: the average student category shifted from "medium" (50%) to "high" (63%) after using Kahoot!. This demonstrates that Kahoot! is effective in enhancing learning interest among fifth-grade students at SDN Nyormanis 2. Therefore, teachers are encouraged to innovate their teaching methods by incorporating engaging activities like games and quizzes using applications such as Kahoot! Keywords: Interest learning, Kahoot!